2001
DOI: 10.1089/08927790152596316
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Uropathy in the Transplanted Kidney: Definitive Management with Percutaneous Nephrostomy and Prolonged Ureteral Stenting

Abstract: Percutaneous nephrostomy and ureteral stenting is a safe and effective treatment for renal allograft obstructive uropathy. Prolonged ureteral stenting may offer a definitive treatment with low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Regan et al 3 also performed routine stent insertion and stated that stents caused less symptoms or complications and prevented morbidity. Pappas et al 2 did not perform routine stent insertion and experienced ureteric obstruction in 15 of the 932 patients only, which they could manage successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Regan et al 3 also performed routine stent insertion and stated that stents caused less symptoms or complications and prevented morbidity. Pappas et al 2 did not perform routine stent insertion and experienced ureteric obstruction in 15 of the 932 patients only, which they could manage successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Pappas et al . [12] managed obstructive uropathy in transplanted kidneys with percutaneous nephrostomy and prolonged ureteric stenting. After prolonged ureteric stenting (mean duration 15 months), there was no recurrence of obstruction in six of eight patients.…”
Section: Discussionmentioning
confidence: 99%
“…[9] reported that 13 patients underwent dilatation with (nine patients) or with no (four) diathermic incision, only the four patients treated with dilatation had recurrent obstruction, while the nine treated with dilatation and incision had no obstruction recurrence (mean follow-up 58 months, range there was no recurrence of obstruction in six of eight patients. The outcomes of published reports (with more than five patients) on endoscopic management for ureteric obstruction in transplanted kidneys are summarized in Table 2 [6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The total long-term success rate was 68%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations